Method for providing background traffic using IP random assigning in cyber range. Issue 6 (23rd February 2021) - Lee, Changwon
Abstract: This letter proposes a method for providing non‐periodic background traffic applicable to cyber ranges. Background traffic is essential to cyber ranges, but it should not be easily distinguished from malicious traffic. The proposed method removes the repetition period of background traffic by using a random number and random shuffling. Details of concatenating traffic data using random numbers and random permutations are presented. Fisher's exact test was conducted to test whether the periodicity of the traffic changes by applying the proposed method, and the results are also illustrated.